Prognostic significance of Zinc finger E-box binding homeobox 1 (ZEB1) expression in cancer cells and cancer-associated fibroblasts in pancreatic head cancer - Bronsert, Peter; Kohler, Ilona; Timme, Sylvia; Kiefer, Selina; Werner, Martin; Schilling, Oliver; Vashist, Yogesh; Makowiec, Frank; Brabletz, Thomas; Hopt, Ulrich T.; Bausch, Dirk; Kulemann, Birte; et al. (Surgery, 2014)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by an aggressive biology and poor prognosis. Experimental evidence has suggested a role for the transcriptional repressor Zinc finger E-box binding homeobox 1 (ZEB1) in epithelial-mesenchymal transition, invasion, and metastasis in PDAC. ZEB1 expression has been observed in cancer cells as well as stromal fibroblasts. Our study aimed to evaluate the prognostic value of ZEB1 expression in PDAC tissue.Patient baseline and follow-up data were extracted from a prospectively maintained database. After clinicopathologic re-review, serial sliced tissue slides were immunostained for ZEB1, E-cadherin, vimentin, and pan-cytokeratin. ZEB1 expression in cancer cells and adjacent stromal fibroblasts was graded separately and correlated to routine histopathologic parameters and survival after resection.A total of 117 cases of PDAC were included in the study. High ZEB1 expression in cancer cells and in stromal cancer-associated fibroblasts was associated with poor prognosis. There was also a trend for poor prognosis with a lymph node ratio of greater than 0.10. In line with its role as an inducer of epithelial-mesenchymal transition, ZEB1 expression in cancer cells was positively correlated with Vimentin expression and negatively with E-Cadherin expression. In multivariate analysis, stromal ZEB1 expression grade was the only independent factor of survival after resection.Our data suggest that ZEB1 expression in cancer cells as well as in stromal fibroblasts are strong prognostic factors in PDAC. Stromal ZEB1 expression is identified for the first time as an independent predictor of survival after resection of PDAC. This observation suggests that therapies targeting ZEB1 and its downstream pathways could hit both cancer cells and supporting cancer-associated fibroblasts.
EVALuna2:10194